The Oxytocinergic System as a Mediator of Anti-stress and Instorative Effects Induced by Nature: The Calm and Connection Theory - Grahn, Patrik; Ottosson, Johan; Uvnäs-Moberg, Kerstin (Frontiers in Psychology, 2021)
Ever more research results demonstrate that human health and well-being are positively affected by stays in and/or exposure to natural areas, which leads to a reduction in high stress levels. However, these natural areas must meet certain qualities. The qualities that are considered to be most health-promoting are those that humans perceive in a positive way. Theories about how natural areas can reduce people's stress levels and improve their coping skills have mainly focused on how certain natural areas that are perceived as safe reduce the activity of the hypothalamo-pituitary-adrenal axis and consequent reduction of cortisol levels. This article discusses studies containing descriptions of how participants in rehabilitation perceive and react to natural phenomena. The common core variable in the analyzed studies was the experience of calm and connection, and this experience was associated with a reduction in stress levels and with being able to develop health and coping skills. We suggest that this experience provides a possible role for the oxytocinergic system to act as a physiological mediator for the positive and health-promoting effects in humans caused by nature. The theory is mainly based on analogies framed by theories and data from the fields of environmental psychology, landscape architecture, and neuroscience. Oxytocin promotes different kinds of social interaction and bonding and exerts stress reducing and healing effects. We propose that oxytocin is released by certain natural phenomena experienced as positive to decrease the levels of fear and stress, increase levels of trust and wellbeing, and develop attachment or bonding to nature. By these effects’ oxytocin will induce health promoting effects. In situations characterized by low levels of fear and stress in response to release of oxytocin, the capacity for “growth” or psychological development might be promoted. Such an instorative effect of nature, i.e., the capacity of nature to promote reorientation and the creation of new coping strategies might hence represent an additional aspect of the oxytocin linked effect profile, triggered in connection with certain nature phenomena. We conclude by proposing that the stress relieving, health promoting, restorative and instorative effects of nature may involve activation of the oxytocinergic system.